MANAGEMENT OF GIANT TUBERCULOMA IN A YOUNG PAPUAN MAN: CASE REPORT AND LITERATURE REVIEW - Bolly, Hendrikus Masang Ban; Sulelino, Renny (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Tuberculoma infection in Papua is still quite high. Tuberculoma is a focus of caseous tubercles found in the brain parenchyma caused by the bacteria Mycobacterium tuberculosis. This study aims to report the outcomes of tuberculosis patients who underwent craniotomy resection of large tuberculoma lesions and continued with therapy using anti-tuberculosis drugs (OAT). There are challenges in the radiological and clinical diagnostic approaches to tuberculoma lesions in these patients who have no history of previous pulmonary tuberculosis infection. A definite diagnosis of tuberculoma is obtained from the establishment of anatomical pathology diagnostics so that the patient is then given FDC category I of anti-tuberculosis drugs for up to 9 months. The patient showed clinical improvement and brain tissue repair after surgery as evidenced by neuroimaging evaluation 7 months after surgery. Management of tuberculosis in Papua requires an educational focus on increasing the synergy of promotive and preventive aspects and finding new cases of tuberculoma to be treated as early as possible.